Impact of web-based health education on HPV vaccination uptake among college girl students in Western and Northern China: a follow-up study - Xi Zhang; Hui Chen; Jing Zhou; Qian Huang; Xiao-yu Feng; Jing Li (BMC, 2022)
Abstract Objective To investigate the effect of a web-based educational intervention on changing female college students' willingness and uptake of human papillomavirus (HPV) vaccines, and factors associated with HPV vaccination acceptance in Western and Northern China. Methods A web-based cluster randomized controlled trial was conducted in Western and Northern China from February to May 2020. A total of 967 female freshmen were recruited from two universities through convenience sampling, stratified sampling (liberal arts or sciences), and cluster sampling. Eligible students were randomized into intervention and control group with a 1:1 allocation ratio. The intervention group received seven days of web-based health education regarding HPV and HPV vaccines, whereas the control group received non-HPV-related materials. All students were asked to complete a post-intervention questionnaire to measure their awareness, uptake, and willingness to receive HPV vaccination at 7-day and one-month intervals. The chi-square test and Student's t-test were employed to examine the differences between the intervention and control groups for categorical and continuous data. Logistic regressions were used to analyze factors associated with vaccination intentions. Results Nine hundred forty-six female freshmen aged 18.99 ± 0.63 years were enrolled in the study, with 532 in the intervention group and 414 in the control group. Prior to the intervention, 63.8%, 66.3%, and 60.8% of students had heard of HPV, HPV-related diseases, and HPV vaccines, respectively. Only 2.2% of students reported being vaccinated, but 33.0% were willing to be vaccinated against HPV. After seven days of education, students in the intervention group exhibited higher awareness (p < 0.001) and knowledge scores (5.13 ± 1.23 vs. 3.10 ± 1.99, p < 0.001) than those in the control group. Similarly, in the intervention groups, willingness to be vaccinated against HPV was significantly higher than in the control groups (p < 0.001). The high cost (57.7%) and concerns about adverse events (56.0%) were the main reasons female college students did not accept HPV vaccines. School location in urban areas, parents' higher education backgrounds, history of HPV vaccination counseling, history of sexual behavior, and having heard of HPV vaccines were associated with a higher willingness to be vaccinated. Conclusion Female college students' HPV vaccination uptake is insufficient, and they have minimal detailed knowledge about HPV and its vaccines. Web-based health education on HPV vaccines is an easy, feasible, and effective way to improve the awareness and acceptance of HPV vaccination among female college students, but it has limited effect on HPV vaccination uptake.